2021
DOI: 10.1002/adfm.202100093
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Injectable Hydrogel Dressings for Effectively Accelerating Wound Healing: Enhancing Biomineralization Strategy

Abstract: Bacterial infection can cause chronic nonhealing wounds, which may be a great threat to public health. It is highly desirable to develop an injectable wound dressing hydrogel with multifunctions including self‐healing, remodeling, antibacterial, radical scavenging ability, and excellent photothermal properties to promote the regeneration of damaged tissues in clinical practice. In this work, dopamine‐modified gelatin (Gel‐DA) is employed for the first time as a biotemplate for enhancing the biomineralization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 56 publications
1
125
0
Order By: Relevance
“…Taken together, these results demonstrate that AgNP hydrogel promotes wound healing, which is consistent with a previous study using a planktonic bacteria wound model, which also showed an improved rate of wound closure in response to AgNP hydrogel treatment [ 59 ]. These results could be attributed to the combined effect of hydrogel biocompatibility and cell proliferative and antibacterial properties of ultra-small AgNPs to effectively eliminate bacterial pathogens and allow wound regeneration.…”
Section: Resultssupporting
confidence: 92%
“…Taken together, these results demonstrate that AgNP hydrogel promotes wound healing, which is consistent with a previous study using a planktonic bacteria wound model, which also showed an improved rate of wound closure in response to AgNP hydrogel treatment [ 59 ]. These results could be attributed to the combined effect of hydrogel biocompatibility and cell proliferative and antibacterial properties of ultra-small AgNPs to effectively eliminate bacterial pathogens and allow wound regeneration.…”
Section: Resultssupporting
confidence: 92%
“…Considering the successful application of enhancing antibacterial and antioxidant strategies in the development of new multifunctional hydrogel wound dressings, [7,10,46] the antibacterial and antioxidant performances of CS-based hydrogels were further evaluated. First, the antibacterial properties of pure CS hydrogels, CA-TA NEs hydrogels and CA-TA-ZA NSs hydrogels were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…To promote wound healing, many dressings have been developed to control infection, promote hemostasis, and improve angiogenesis [ 132 , 133 , 134 ]. The development of hydrogel with excellent antibacterial properties, good compatibility, and degradable ability is a promising strategy for wound healing [ 135 , 136 ]. Hydrogels with a photothermal conversion ability can regulate the temperature by changing the NIR irradiation intensity/time, photothermal initiator concentration/ratio, and cycling time [ 137 , 138 ].…”
Section: Photothermal Hydrogels In Wound Healing and Bone Repairmentioning
confidence: 99%